2017
DOI: 10.1111/ijfs.13554
|View full text |Cite
|
Sign up to set email alerts
|

The influence of flaxseed gum on the retrogradation of maize starch

Abstract: The influence of flaxseed gum (FG) on the retrogradation of maize starch (MS) was investigated in this study. Based on the results of rapid visco-analyzer (RVA), differential scanning calorimetry (DSC), X-ray diffraction (XRD), Low field nuclear magnetic resonance (LF-NMR) and scanning electron microscopy (SEM), FG has a retardation effect on the retrogradation of MS. With the addition increasing, the more significant the retardation effect was observed (P < 0.05). However, when the concentration of FG was up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
5
22
0
Order By: Relevance
“…According to Aguirre et al (2011), starch gels stored at 4°C have the highest crystallinity value and the highest growth rate of these values. 1 shows that the FG addition could effectively inhibit the recrystallisation of MS starch, which is consistent with the results of our previous study (Yang et al, 2017). This result indicated that the network of starch gels was fixed quickly under low-temperature storage, thereby leading to a decrease in nucleation and propagation rate (Shifeng et al, 2012).…”
Section: Recrystallisationsupporting
confidence: 90%
See 1 more Smart Citation
“…According to Aguirre et al (2011), starch gels stored at 4°C have the highest crystallinity value and the highest growth rate of these values. 1 shows that the FG addition could effectively inhibit the recrystallisation of MS starch, which is consistent with the results of our previous study (Yang et al, 2017). This result indicated that the network of starch gels was fixed quickly under low-temperature storage, thereby leading to a decrease in nucleation and propagation rate (Shifeng et al, 2012).…”
Section: Recrystallisationsupporting
confidence: 90%
“…Research has shown that a higher relative amount of neutral polysaccharides, such as xylose, can enhance the rheological properties of FG by mitigating shear thinning and weak gel properties (Cui et al, 1994). FG can wrap around starch granules, suppress the recrystallisation of amylose and amylopectin, increase water mobility and decrease water loss (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no significant change in the results of T 21 and T 22 of RS/XT‐GCSPHs, indicating that the combined XT and GCSPHs could suppress the mobility of free water decrease the loss of water molecules, and prevent the proportion of amorphous regions from transforming to crystalline regions to inhibit starch retrogradation . And the normalized peak area (A 21 , A 22 , and A 23, Table ) confirmed the results of T 21 and T 22.…”
Section: Resultssupporting
confidence: 52%
“…According to Fu et al, Wang et al, and Dias et al, the retrogradation of starch gel result in the loss of water content, especially higher mobility water. Therefore, as reported in previous literatures, the T 2i relaxation time determined by LF‐NMR with a sequence of CPMG is often applied to evaluate the diverse mobility and microscopic distributions of the various fractions of water in starch gels. The smaller the T 2i is, the weaker the mobility of the corresponding water is.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation